2013
DOI: 10.1007/s00520-013-1717-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for overall quality of life in patients with advanced cancer

Abstract: Deterioration of certain EORTC QLQ-C15-PAL functional/symptom scores significantly contributes to worse overall QOL. Special attention should be directed to managing factors most influential on overall QOL to ensure optimal management of advanced cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 28 publications
3
46
0
2
Order By: Relevance
“…Multiple studies have found pain to be a determinant of quality of life in patients with cancer. 11,44,45,52,62 Furthermore, neuropathic pain has a greater effect on quality of life than nociceptive pain. 53 Identification of the type of pain experienced by chordoma patients will be important in achieving improvement in quality of life through pain control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have found pain to be a determinant of quality of life in patients with cancer. 11,44,45,52,62 Furthermore, neuropathic pain has a greater effect on quality of life than nociceptive pain. 53 Identification of the type of pain experienced by chordoma patients will be important in achieving improvement in quality of life through pain control.…”
Section: Discussionmentioning
confidence: 99%
“…The GOSE classifies function into 1 of 8 categories with lower scores indicating a worse disability (1, To determine states of anxiety and depression, the Patient Health Questions-9 (PHQ-9) instrument was administered. 32 Based on participant responses to 9 questions, the severity of depression can be categorized into minimal (a score of 1-4), mild (a score of 5-9), moderate (a score of [10][11][12][13][14], moderately severe (a score of [15][16][17][18][19], and severe (a score of [20][21][22][23][24][25][26][27]. The 22-item Zarit Burden Interview (ZBI) was used to measure the level of subjective burden among caregivers.…”
Section: Instrumentsmentioning
confidence: 99%
“…(1-3) Since painful bone metastases have a major impact on quality of life (QoL) in patients with advanced cancer (4,5), reducing pain is likely to improve QoL. Although a few studies showed that radiotherapy for painful bone metastases contributes to improvement of QoL, no thorough studies have been published focusing on the course of QoL after radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although reduction of pain is the main treatment goal, it is also important to focus on quality of life (QoL) [4]. Painful bone metastases have a negative impact on the QoL of patients [5,6]. Studies show that radiotherapy stabilizes or improves QoL [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%